D-dimer Quantification from Autologous Red Blood Cells Agglutination by a Lens-free Imaging Device. (2017) - Huet, M.; Cubizolles, M.; Pouteau, P.; Poher, V.; Buhot, A.
Abstract: Quantification of biomarkers closest to the patient remains an impressive challenge for the development of personalized medicine. The detection of D-dimer, a fibrin degradation product, indicative of deep vein thrombosis, pulmonary embolism or stroke is a particular biomarker of interest. In this study, we developed a quantitative assay based on the measurement of autologous red blood cells agglutination by a lens-free device. An indicator, obtained from the shape of the gray level histogram of the images, allows us for a linear quantification of D-dimer opening the door for a Point-of-Care device.